(untitled) (Journal of the College of Basic Education, 2022)
Reason for my choice of topic is that reform is the most I’m poor tent reason for a decent life for society .The ere fore ,it has taken the reasons that help society to reach these causes .The problem of lack of reform in society is one of the problems that are the bus is for the collapse of societies and moving a was from main source in solving this problem constitutes a danger to societier . The importance of research The importance of the corruption she’ll in the right way means the correct course of life and in a way that serves society to reach the best way of life Research objectives :one of the most important objectives of the research is to return to the source of correct reforms the Holy Qur’an because the in introduction of human laws and jurisprudence that did hot present society with problems and woes that we did not benefit from, but on the contrary, we have come back to our inclusion and move away from the cliff firem The most important means of date collection:- The Hole Qur’an interpretations juistts.Books .ma Theses The most important conclusions Reform is not an impossible thing ,but it is an application of the rules that help reform and its source is the Holy Quran which is a constitution that works for every time and place.Then one of the most important reasons for reform is self -reforming by implementing the correct principles ,starting with schools, mosques and other institutions stave off an epidemic of corruption from society